The impact of e-service quality on e-loyalty through the mediating effects of e-satisfaction and e-trust in Lebanon - Chmeis, Suzanne; Zaiter, Rushdi (Technium Social Sciences Journal, 2024)
businesses to reach customers. E-service quality is an online company's customer service. It includes website design, navigation, responsiveness, security, dependability, and customer support. E-commerce has grown due to its convenience, speed, and accessibility. Online businesses' success depends on e-service quality. When e-services are good, customers return. Poor e-service quality can occur. Poor e-service quality can turn customers away. Online businesses must offer high-quality e-services to satisfy customers and stay competitive. E-service quality affected e-loyalty. Website efficiency—ease of use, organization, and quick access—and website information quality—accuracy, frequency, clarity, and relevance—measure e-service quality. E-service quality dimensions affect e-satisfaction and e-trust, which are necessary for e-loyalty. The research model's variables' influencing factors were also examined. The quantitative study surveyed Lebanon's online shoppers using a validated questionnaire. 2378 Lebanese from various backgrounds participated in the study. T-test, ANOVA, and SEM were used to analyse SPSS data. This study is important because the pandemic and lockdowns have changed consumer purchasing behaviour. Customers are more critical of e-commerce platforms and more comfortable using multiple devices to access online stores and apps as they shop more online. This study is timely and relevant for businesses trying to stay competitive in the changing e-commerce landscape due to consumer behaviour changes. Both e-service quality dimensions are positively correlated with e-loyalty determinants e-trust and e-satisfaction. E-trust and e-satisfaction both have positive and significant relationships with e-loyalty, but e-satisfaction had a stronger effect. Through e-satisfaction and e-trust, e-service quality dimensions indirectly affect e-loyalty.